Filaments in the edge confinement region of TJ-II. (5th January 2018) - van Milligen, B.Ph.; Nicolau, J.H.; Liu, B.; Grenfell, G.; Losada, U.; Carreras, B.A.; García, L.; Hidalgo, C.
Abstract: Floating potential measurements from two remote reciprocating probes in the plasma edge region of the TJ-II stellarator are analyzed using the transfer entropy, revealing the spatial dimensions and propagation properties of filamentary structures. The results are corroborated by performing simulations with a resistive MHD model and analyzing data from synthetic diagnostics. The transfer entropy captures the rotation of the filaments and allows the calculating of their rotation velocity. This deduced velocity was compared to the (known) poloidal velocity of the plasma and showed a relatively good agreement.